Oriented Skill System of Continuing Education for Teachers of Higher Education [Sistema de Perfeccionamiento Orientado a Competencias Para Docentes de la Educación Superior] - Palominos-Villavicencio, F; Barrera-Capot, R (Centro de Informacion Tecnologica, 2014)
The paper presents an oriented skill system of continuing education for teachers of higher education intended to support the modernization of teaching in undergraduate and graduate levels. Considering several previous experiences, factors that often adversely affected or impeded the success of the development and innovation are identified. The various elements of the system are designed to neutralize or reduce these factors, relying on a diagnostic process properly contextualized, identifying meaningful goals and process planning which in agreement with institutional policy allow generating the appropriate conditions for innovation and change. The results show that the system can properly identify development needs, considering the cultural factors of the institution.